Aging, Resting Pulse Rate, and Longevity. Issue 1 (10th January 2013) - Stessman, Jochanan; Jacobs, Jeremy M.; Stessman‐Lande, Irit; Gilon, Dan; Leibowitz, David
<x xml:space="preserve">Abstract</x> Objectives To examine the relationship between resting pulse rate (RPR) and longevity in individuals aged 70 to 90. Design The Jerusalem Longitudinal Cohort Study (1990–2010) is a prospective longitudinal study of a representative cohort born in 1920–21. Setting Home‐based comprehensive assessment in 1990, 1998, and 2005. Participants Individuals aged 70 (n = 453), 78 (n = 856), and 85 (n = 1, 044), with follow‐up to age 90. Measurements Comprehensive assessment included average RPR, beta‐blocker usage, and physical activity level. Mortality data were collected from the Ministry of Interior from 1990 to 2010. Methods Cox proportional hazards ratios (HRs) were determined for RPR (continuous variable), adjusting for sex, education, diabetes mellitus, ischemic heart disease, congestive heart failure, hypertension, kidney disease, anemia, physical activity, body mass index, self‐rated health, dementia, beta‐blocker use, and an interaction term for RPR by beta‐blocker use. Results Mean RPR was 75.1 ± 9.9 at 70, 74.5 ± 10.9 at 78, and 68.5 ± 10.5 at 85 in women and 74.3 ± 10.7 at 70, 73.1 ± 11.2 at 78, and 65.2 ± 10.5 at 85 in men, with a significant decline from 78 to 85 for both sexes. In participants not taking beta‐blockers followed up from 70 to 77, 78 to 84, and 85 to 90, mean RPR was lower in survivors than nonsurvivors for women (75.8 ± 9.2 vs 83.5 ± 10.9, P < .001; 75.2 ± 9.8 vs 79.9 ± 12.6, P = .004; 71.5 ± 9.9 vs 74.6 ± 10.7, P = .02, respectively) and men (75.2 ± 10.3 vs 75.2 ± 10.9, P = .98; 73.5 ± 10.1 vs 77.2 ± 12.1, P = .005; 67.1 ± 9.5 vs 70.4 ± 11.7, P = .01, respectively). Adjusted HRs for mortality per 10‐beat increase in RPR during follow‐up were 1.13 (95% confidence interval (CI) = 0.87–1.47) for 70 to 77, 1.35 (95% CI = 1.11–1.65) for 78 to 84, and 1.17 (95% CI = 1.01–1.37) for 85 to 90. Conclusion RPR declines in the oldest old, and this decline is associated with greater longevity. It may serve as a simple prognostic marker in the oldest old.